EVALUATION REINFORCER MAGNITUDE AND RATE DEPENDENCY OF RESISTANCE TO CHANGE MECHANIMS - Pinkston, Jonathan W. (Behav Pharmacol, 2014)
In many circumstances, reinforcer magnitude appears to modulate the rate-dependent effects of drugs, such that when schedules arrange for relatively larger reinforcer magnitude, rate dependency is attenuated compared to behavior maintained by smaller magnitudes. The current literature on resistance to change suggests that increased reinforcer density strengthens operant behavior, and such strengthening effects appear to extend to the temporal control of behavior. As rate dependency may be understood as a loss of temporal control, the effects of reinforcer magnitude on rate dependency may be due to increased resistance to disruption of temporally controlled behavior. In the present experiments, pigeons earned different magnitudes of grain during signaled components of a multiple fixed-interval schedule. Three drugs, clonidine, haloperidol, and morphine, were examined: all three decreased overall rates of key pecking; however, only the effects of clonidine were attenuated as reinforcer magnitude increased. An analysis of within-interval performance found rate-dependent effects for clonidine and morphine, but those effects were not modulated by reinforcer magnitude. Additionally, we included prefeeding and extinction conditions, standard tests used to measure resistance to change. In general, rate-decreasing effects of prefeeding and extinction were attenuated by increasing reinforcer magnitudes. Rate-dependent analyses of prefeeding showed rate-dependency following those tests, but in no case were these effects modulated by reinforcer magnitude. The results suggest a resistance-to-change interpretation of the effects of reinforcer magnitude on rate dependency is not viable.